2011
DOI: 10.5530/ax.2011.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging and Anti-lipid Peroxidative Effects of a Hydro-ethanolic Extract of the Whole Plant of Synedrella nodiflora (L.) Gaertn (Asteraceae)

Abstract: Background: Synedrella nodiflora (L.) Gaertn. (Asteraceae), a native Ghanaian shrub, has been used for the treatment of epilepsy, hiccup and threatened abortion. The present study aimed at investigating the possible mechanisms of antioxidant effects of the hydro-ethanolic extract of the whole plant. Methods: Total phenolic content was determined using the FolinCiocalteau assay and the antioxidant capacity by the phosphomolybdenum method. The antioxidant activity was evaluated by the 1, 1-diphenyl-2-picryl-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…AFS.2015.4.32 high phenolic compounds content showed by this extract. Amoateng et al (2011) reported that DPPH scavenging ability of Synedra nodifl ora (Asteraceae family) extracted in ethanol solvent (70%) is about 0.31 mg/ml of extract, suggesting that our results are more important. In the DPPH…”
Section: Antioxidant Activity Of S Undulata Extractsmentioning
confidence: 84%
“…AFS.2015.4.32 high phenolic compounds content showed by this extract. Amoateng et al (2011) reported that DPPH scavenging ability of Synedra nodifl ora (Asteraceae family) extracted in ethanol solvent (70%) is about 0.31 mg/ml of extract, suggesting that our results are more important. In the DPPH…”
Section: Antioxidant Activity Of S Undulata Extractsmentioning
confidence: 84%
“…The total phenolic content of the crude extract (SNE) was assayed by the Folin Ciocalteu's method, as published by Amoateng et al, 2011 [5] with slight modifications. An aliquot (10 ”l) of the extract (20 mg/ml) was placed into an Eppendorf tube, to which 0.79 ml of distilled water was added.…”
Section: Total Phenol Assaymentioning
confidence: 99%
“…In Ghana, the whole plant is boiled, and the aqueous extract drunk for the treatment of neurological conditions such as epilepsy, whiles the leaves are used for threatened abortion, hiccup, laxative and as feed for livestock [1]. The crude hydro-ethanolic extract of this whole plant has been found to possess anticonvulsant [3], sedative [4], antioxidant [5], anti-nociceptive properties [6,7] and anti-proliferative effects on onion root and shoot apical meristem and wister rat bone marrow cells [8]. Hence, this study seeks to investigate further the antioxidant potential and anti-proliferative activities of various fractions of the hydro-ethanolic extract of this plant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after in vitro digestion, the polyphenols could have been degraded by the alkaline pH and subsequent decrease in the TPC, TFC and the antioxidant capacity (Bobrich et al, 2014). The degradation of bioactive compounds may also come from enzymatic reactions in the sample, resulting in the degradation of bioactive compounds (Amoateng, Assumeng-Koffuor, Sarpong, & Oteng-Agyapong, 2011). Likewise, the processing effect on potential bio-accessibility of antioxidant capacity and bioactive compounds can exert a positive or negative effect, depending on the food matrix in the processing conditions (Lafarga, VillarĂł, Bobo, SimĂł, & AguilĂł-Aguayo, 2019).…”
Section: Antioxidant Capacity and In Vitro Potential Bio-accessibilitmentioning
confidence: 99%